PENGARUH CR, DER, DAN NPM TERHADAP HARGA SAHAM DENGAN EPS SEBAGAI VARIABEL MODERASI - Nisa Nur Laylia; Misbahul Munir (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research aims to find out how the influence of Current Ratio (CR), Debt To Equity Ratio (DER), and Net Profit Margin (NPM) on Stock Prices With Earnings Per Share (EPS) as Moderation Variables (Studies on Manufacturing Companies Of Consumer Goods Industry Subsectors Listed on the IDX For the Period 2018-2020). The analysis method used is with multiple regression analysis, and classical assumption tests that include normality tests, multicolonierity tests, heterochemicity tests and autocorrelation tests. Finally, hypothesis testing is carried out which includes simultaneous significant tests (F tests), and t tests. The results of this study show that (1) CR has no significant influence on stock prices, (2) DER has no significant influence on stock prices, (3) NPM has no significant influence on stock prices, (4) EPS does not strengthen the relationship between Current Ratio (CR), Debt To Equity Ratio (DER), and Net Profit Margin (NPM) to stock prices.